EFFECT OF WALNUT AND SAFFLOWER OIL ON LIPID PROFILE AND GLUCOSE LEVEL IN MALE WISTAR RATS - Dina M Trabzuni; Shaista Arzoo; Islam Abdul Rahim Saad el Dien el Redh; Mervat Mohammad ElSayed; Amal A Aloud (IJRDO-Journal of Applied Science, 2020)
In the recent decades research on consumption of dietary fats and oil has become an important topic for discussion. This study was carried out to determine the effects soybean (SOBO), walnut (WALO) and safflower (SAFO) oil on lipid profile and glucose level in male Wistar rats. Fifteen male Wistar rats weighting between 150-170 grams were divided randomly into three groups of five rats each. Groups 1 (Control group, SOBO) was assigned to receive 30 grams of the control diet with soybean oil per day. Group 2 was allocated to take 30 grams of the diet with walnut oil per day and group 3 was allocated to receive 30 grams of the diet with safflower oil per day. Statistically insignificant difference was observed between control (SOBO group) and experiments groups (WALO and SAFO) for all growth parameters. Least value of HDL-C was observed in SOBO group and the highest value was found in WALO group but the difference was insignificant between the groups. TG, LDL-C and VLDL-C was least in SAFO group and lowest value of cholesterol was observed in WALO group but the difference for TC, TG, LDL-C, VLDL-C glucose and insulin was also statistically insignificant the groups. In this study even though insignificant but improvement in blood lipid profiles has been observed without altering other dietary components.